Design of high efficiency energy harvesting circuit using dual switching technique. (2021) - Vithya Lakshmi, N.; Vinoth, G.S.; Binoj, J.S.; Manikandan, N.
Highlights: Dynamic Bulk Switching. Reverse Leakage Current. Dual MOS Transistor. Power Conversion Efficiency. Energy harveting. Abstract: Energy harvesting technique has been popularly used as a powering methodology for various low power applications like wireless sensor nodes, wearable and implantable devices. This paper mainly focuses novel rectifier design to enhance the performance of energy harvesting circuit. The sound signals produced from smartphone or loud speaker are the main input source for the energy harvesting circuit consisting of transducer, rectifier, regulator. The existing active diodes of rectifier are replaced with dual switching technique. This technique maintains constant gate bias, reduces reverse leakage current and area and increases the power conversion efficiency of rectifier. The proposed rectifier yields maximum power conversion efficiency (PCE) of 85% with an input voltage of 800mv. The energy harvesting circuit has been designed and simulated within CMOS standards.